1995
DOI: 10.1007/bf00010127
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of localized phosphorus-patches by common bean roots

Abstract: Phosphorus (P) uptake from patches was investigated in high-P and low-P common bean (Phaseolus vulgaris L.) plants using a split-root system . A P-patch was developed by exposing a small sub-section of the root system to localized P enrichment . A soil-based media was used to provide realistically low, buffered levels of P In addition, nutrient solution provided zero and 1 mM P to low-P and high-P plants, respectively . Overall, growth of low-P plants was approximately 40% that of high-P plants . Mycorrhizal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 31 publications
1
20
0
5
Order By: Relevance
“…Thus, for example, an external supply of 1 mM NO 3 − stimulated lateral root growth more strongly in barley when the remainder of the root system was in low NO 3 − than if it too was in high NO 3 − (Drew et al, 1973). Similarly, roots of P-stressed bean plants presented with a P-enriched soil patch branched more intensively within the patch than did roots of unstressed plants (Snapp et al, 1995).…”
Section: Root Growth and Branchingmentioning
confidence: 89%
“…Thus, for example, an external supply of 1 mM NO 3 − stimulated lateral root growth more strongly in barley when the remainder of the root system was in low NO 3 − than if it too was in high NO 3 − (Drew et al, 1973). Similarly, roots of P-stressed bean plants presented with a P-enriched soil patch branched more intensively within the patch than did roots of unstressed plants (Snapp et al, 1995).…”
Section: Root Growth and Branchingmentioning
confidence: 89%
“…Many authors have measured the structural response of root systems to the levels of nutrient that is available to them [15], [35], [114], [106]. The majority find that an increase in phosphate level leads to the first order root branch density increasing in order to exploit the soil more effectively, but the root length is generally thought to be less affected by the nutrient level in the soil [15].…”
Section: Root Structure In Relation To Nutrient Uptakementioning
confidence: 99%
“…The majority find that an increase in phosphate level leads to the first order root branch density increasing in order to exploit the soil more effectively, but the root length is generally thought to be less affected by the nutrient level in the soil [15]. However, some studies [35], [114] have found that the length is also affected.…”
Section: Root Structure In Relation To Nutrient Uptakementioning
confidence: 99%
“…Surprisingly little attention however has been given to the latter process, and in only one previous study (Schwartz et al, 1999) has the possibility that the root growth of hyperaccumulator plants may respond positively to metal enriched soil been examined. Active foraging for the macronutrients nitrogen and phosphorus, by means of enhanced root growth and root branching in nutrient enriched patches, has been demonstrated in many species (Drew & Saker, 1975 ;Granato & Raper, 1989 ;Gross et al, 1993 ;Snapp et al, 1995), and is reviewed in detail by Robinson (1994). Indeed, Zhang & Forde (1998) have identified a gene (ANR1) which encodes for increased lateral root proliferation in localized patches of nitrate (NO $ − ).…”
Section: mentioning
confidence: 99%